Pengaruh Media Pembelajaran ICT Wordwall Terhadap Hasil Belajar IPAS Pada Materi Berkenalan Dengan Energi Di Kelas III SDN Cengklik Surakarta - Anghelica, Shilvia Mareta; Handini, Oktiana; Restuningsih, Ani (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The purpose of this study was to determine the effect of ICT Wordwall learning media on student learning outcomes in the Natural and Social Sciences (IPAS) subject,